Analisis Penanganan Traffic Operasi Penerbangan Unit AMC pada Event MotoGP 2024 di Bandara Lombok - Robiawal Safutra; Andityo Pujo Laksana (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
In organizing the MotoGP Event at Zainuddin Abdul Madjid International Airport, Lombok, a significant increase in flight traffic affects operational capacity, especially in the Apron area. The Apron Movement Control (AMC) Unit plays a crucial role in ensuring the smooth and safe movement of aircraft, vehicles, and personnel. During the event, the surge in passenger numbers and aircraft movements puts additional pressure on the AMC, making it essential to maintain operational safety and efficiency in the apron area. This study aims to determine how the handling of increased flight traffic affects the efficiency of apron space usage during the 2024 MotoGP Event and what strategies and mechanisms are implemented by the Apron Movement Control (AMC) Unit in increasing the efficiency and safety of flight operations during the 2024 MotoGP Event at Zainuddin Abdul Madjid International Airport. This study uses a qualitative method. The data used in this study are primary data and secondary data. Data collection techniques used in this study are observation, interviews and documentation. Based on the research, it can be concluded that the role of Apron Movement Control (AMC) at Zainuddin Abdul Madjid Lombok International Airport during the 2024 MotoGP Event is very vital for the smooth running of flight operations, especially in managing increased traffic. AMC is tasked with following established procedures, including aircraft parking arrangements and efficient use of apron space. To overcome the spike in traffic, AMC added personnel, increased supervision in the airside area, and coordinated with relevant stakeholders, including Airnav Indonesia. In addition, airport infrastructure was expanded and operations were improved to meet the needs during the event, ensuring that all aircraft movements were safe and orderly.